2013
DOI: 10.1007/s11095-013-1102-8
|View full text |Cite
|
Sign up to set email alerts
|

On-Command Drug Release from Nanochains Inhibits Growth of Breast Tumors

Abstract: Purpose To evaluate the ability of radiofrequency (RF)-triggered drug release from a multicomponent chain-shaped nanoparticle to inhibit the growth of an aggressive breast tumor. Methods A two-step solid phase chemistry was employed to synthesize doxorubicin-loaded nanochains, which were composed of three iron oxide nanospheres and one doxorubicin-loaded liposome assembled in a 100-nm-long linear nanochain. The nanochains were tested in the Luc-GFP-4T1 orthotopic mouse model, which is a highly aggressive bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Recently, it was shown that an 100-nm-long oblong chain-like nanoparticle (termed nanochain) composed of three iron oxide nanospheres and one doxorubicin-loaded liposome exhibited a 2-fold higher extravasation into tumors in a mammary adenocarcinoma model compared to spherical liposomal doxorubicin [93]. In addition, as a result of the multicomponent design of the nanochain, radiofrequency-triggered drug release from the particles resulted in the therapeutic efficacy being three-fold higher than treatments using spherical nanoparticles [93, 147]. Interestingly, the chain-shaped nanoparticle responded in a unique manner in the presence of a magnetic field.…”
Section: Effect Of Nanoparticle Shape On Tumor Deposition and Therapementioning
confidence: 99%
“…Recently, it was shown that an 100-nm-long oblong chain-like nanoparticle (termed nanochain) composed of three iron oxide nanospheres and one doxorubicin-loaded liposome exhibited a 2-fold higher extravasation into tumors in a mammary adenocarcinoma model compared to spherical liposomal doxorubicin [93]. In addition, as a result of the multicomponent design of the nanochain, radiofrequency-triggered drug release from the particles resulted in the therapeutic efficacy being three-fold higher than treatments using spherical nanoparticles [93, 147]. Interestingly, the chain-shaped nanoparticle responded in a unique manner in the presence of a magnetic field.…”
Section: Effect Of Nanoparticle Shape On Tumor Deposition and Therapementioning
confidence: 99%
“…The multicomponent nature and shape of the particle result in two unique features that facilitate effective treatment of difficult-to-treat brain tumors using a low dose of cytotoxic drugs as illustrated in Fig. 1C (7, 9, 10). Contrary to traditional small-molecule drugs or more contemporary nanotherapeutics, the nanochain particle possesses a unique ability to gain rapid access to and be deposited at brain tumor sites.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, which leads to a new ā€˜interferingā€™ signal from EPR-driven deposition of the nanoparticle. To accurately differentiate vascular targeting from signals in the blood pool or deep-tissue, investigators have optimized and identified a low dose of nanoparticles agents that generated significantly detectable signal on the tumor-associated vascular bed and insignificant background ā€œnoiseā€ due to the blood circulation of the nanoparticle or its non-specific uptake in various organs ( e.g ., liver, spleen) [85,88,87]. …”
Section: Disease Pathobiology and Its Influence On The Endotheliummentioning
confidence: 99%